Modal Intelektual dan Kinerja Keuangan dengan Menggunakan Islamicity Performance Index pada Umum Syariah - Puspitosari, Indriyana (State Institute of Islamic Studies (IAIN) Palu, 2016)
The aim of this study is to find the evidence about correlation between intellectual capital and financial performance because of the orientation changing about corporate assets from the tangible asset become intellectual capital. This study uses 9 shariah banking in Indonesia as the sample in period 2011-2014. The intellectual capital variable gauge by modified Pulics model for Islamic banking with three komponen iB-VACA, iB-VAHU and iB-STVA. Profit sharing ratio, zakat performance ratio and Islamic income vs non Islamis income are the proxy of Financiel performance. This study used Pearson Corelation analysis as tools to analyze this corelation. The study finding that between intellectual capotal component and islamicity Performance Index indicatore have the different strength and direction correlation